2013
DOI: 10.1186/1471-2482-13-s2-s21
|View full text |Cite
|
Sign up to set email alerts
|

Elective and emergency laparoscopic cholecystectomy in the elderly: our experience

Abstract: BackgroundWe aimed to analyze outcomes of early and delayed laparoscopic cholecystectomy in the elderly in our General Surgery Division.MethodsWe analyzed 114 LC performed from the 1st of January 2008 to the 31st of December 2012 in our General Surgery division: 67 LC were performed for gallbladder stones and 47 for acute cholecystitis.Results and discussionComparison between Ordinary and Emergency groups showed that drain placement and post-operative hospital stay were significatively different. There were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…All surgeries in this study were performed by experienced attending surgeons. Laparoscopic cholecystectomy [ 15 ] was carried out using four incisions with pneumoperitoneum installed via a sub-umbilical mini-laparotomy with the maximum intraabdominal pressure kept at 12 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…All surgeries in this study were performed by experienced attending surgeons. Laparoscopic cholecystectomy [ 15 ] was carried out using four incisions with pneumoperitoneum installed via a sub-umbilical mini-laparotomy with the maximum intraabdominal pressure kept at 12 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…11 For example, insufflating carbon dioxide during laparoscopy may cause acid-base disturbances and changes in cardiopulmonary physiology that are otherwise avoided in the open approach. [23][24][25] Despite these concerns, systematic studies indicate that laparoscopic procedures in elderly patients offer many advantages, such as lower pain and convalescence, and clinicians still tend to prefer laparoscopy in the elderly in both emergent or elective settings. 11,26,27 Our multivariable linear regression model illustrated that elective admissions, laparoscopic operations, and younger patients were associated with lower hospital stays and total costs.…”
Section: Resultsmentioning
confidence: 99%
“…They found that early intervention was associated with shorter postoperative stay, and no increase in complications rate [17]. Ferrarese et al [18] analyzed the outcome of early and delayed 114 cholecystectomies conducted in their institution. They found laparoscopic cholecystectomy a safe and effective treatment for cholelithiasis and acute cholecystitis in ordinary and emergency settings [18].…”
Section: Operative Management In the Elderlymentioning
confidence: 99%